Optical Properties of Aluminum- and Silicon-Nitride Films and Al–Si–N Nanocomposite Coatings Deposited by Reactive Magnetron Sputtering; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 15, iss. 1 - Konusov F. V. Fedor Valerievich; Pavlov S. K. Sergey Konstantinovich; Lauk A. L. Aleksandr Lukyanovich; Kabyshev A. V. Aleksandr Vasiljevich; Gadirov R. M. Ruslan Mukhamedzhanovich (2021, 2021)
Title screen